Influence of water dilution on performance of chromium polymer weak gel in porous medium. Issue 10 (3rd August 2020) - Xie, Kun; Cao, Weijia; Lu, Xiangguo; Song, Kaoping; Liu, Yigang; Zhang, Yunbao; Liu, Jinxiang; Lv, Jinlong; Wang, Wei; Na, Risu
Abstract: In order to explore the influence of water dilution on performance of Cr 3+ polymer weak gel in porous medium, the performances of pure polymer solution and Cr 3+ polymer weak gel were studied according to the laboratory testing of viscosity, micro-structure performances (polymer molecule aggregate dimension, polymer molecule aggregate configuration and Zeta potential), seepage characteristics and oil displacement effect under the condition of water dilution. The results indicated that, after diluting by water, pure polymer solution and Cr 3+ polymer weak gel had an almost same viscosity, but there were obvious differences in micro-structure performance and seepage characteristics. Different with pure polymer solution, with the decrease of polymer concentration, on the one hand, the influence of free Cr 3+ on electric double layer and shielding effect on electrostatic exclusion got weaker, on the other hand, water molecules were attracted by hydrophilic groups on the Cr 3+ polymer weak gel molecular chains and then entered into the three-dimensional spatial structure of Cr 3+ polymer weak gel, producing hydration and expansion. Therefore, the polymer molecule aggregate dimension of Cr 3+ polymer weak gel presented a trend of continuous increasing. This characteristic was good for keeping the injection pressure at a higher value during diluting in the porous medium, which could be used to improve oil recovery in offshore oilfield through conducting injection of water-alternating- Cr 3+ polymer weak gel. Graphical Abstract: uf0001